Domestic Violence as State Crime : A Feminist Framework for Challenge and Change. - Rose, Evelyn ([Place of publication not identified] : Routledge, 2021)
Domestic Violence as State Crime presents a provocative challenge to the way that domestic violence is understood and addressed. Underpinned by a radical feminist perspective, the central argument of this book is that domestic violence against women constitutes a patriarchal state crime. By analysing the international, collective, structural, and institutional dimensions of this harm, the author outlines a spectrum of state complicity ranging from passive bystander to active producer, participant, and perpetrator. The wide-ranging analysis in this book draws on data from comparable liberal democratic contexts including Australia, the United States, and United Kingdom, in order to comprehensively show how domestic violence state criminality functions in practice éven in the present and in supposedly progressive contexts. This analysis provides valuable insight into why this epidemic-scale crime is ever-resistant to a diversity of contemporary interventions. Drawing its concepts into a cohesive whole, the book then posits an overarching feminist typological theory of domestic violence as state crime. It also considers how domestic violence might be addressed if we confront its state crime dimensions and adopt a more holistic and transformative approach to remedy, redress, prevention, and justice. An accessible and compelling read, Domestic Violence as State Crime offers an innovative scholarly and activist contribution to the study of violence against women, feminism, criminology, and the broader critical study of law, politics, and society. It will appeal to anyone who is interested in thinking differently about domestic violence and the state.
Part One:Domestic violence, feminism, and state crime 1.The need to radically rethink domestic violence 2.Reasserting radical feminism: Being, feeling, knowing, thinking, doing Part Two:The state crime dimensions of domestic violence 3.Domestic violence as state crime against humanity 4.Domestic violence as micro-state crime 5.Domestic violence as structural state crime 6.Domestic violence as omissive institutional state crime 7.Domestic violence as agentic institutional state crime Part Three:Theorising and addressing domestic violence as state crime 8.A typological theory of domestic violence as state crime 9.Responding to domestic violence as state crime
OCLC-licensed vendor bibliographic record.
Keywords: Family violence; FAMILY & RELATIONSHIPS / General; FAMILY & RELATIONSHIPS / Abuse / General; LAW / Family Law / General